U–Pb SHRIMP zircon dating of Grenvillian metamorphism in Western Sierras Pampeanas (Argentina): Correlation with the Arequipa-Antofalla craton and constraints on the extent of the Precordillera Terrane - Casquet, César (2006)
Metamorphism of Grenvillian age (ca. 1.2 Ga; U–Pb zircon dating) is recognized for the first time in the Western Sierras Pampeanas (Sierra de Maz). Conditions reached granulite facies (ca. 780 °C and ca. 780 MPa). Comparing geochronological and petrological characteristics with other outcrops of Mesoproterozoic basement, particularly in the northern and central Arequipa-Antofalla craton, we suggest that these regions were part of a single continental crustal block from Mesoproterozoic times, and thus autochthonous or parautochthonous to Gondwana.